Is Initial Misdiagnosis Associated with Reaching Disability Milestones in Patients with Multiple Sclerosis? - Alina Ivaniuk; Tetiana Marusich; Yuliia Solodovnikova; Anatoliy Son (Medicina, 2020)
Background and objectives: multiple sclerosis (MS) is a chronic demyelinating disorder of the CNS with a variable course and disability progression. The latter may be prevented with disease-modifying therapy (DMT). Initial misdiagnosis may postpone the use of DMT. There are no studies to explore whether initial misdiagnosis is indeed associated with a higher rate of reaching disability in MS patients. We aimed to investigate the association between initial misdiagnosis and reaching disability milestones in relapsing-remitting MS (RR-MS) patients. Materials and methods: Data from 128 RR-MS patients were retrospectively reviewed. EDSS 4 and EDSS 6 were chosen as disability milestones as those associated with a significant decrease in ambulation. Survival analysis was used, and Kaplan–Meier curves were generated to investigate how initial misdiagnosis affects reaching the defined milestones. Results: 53 patients (41.4%, 31 females, 22 males) were initially misdiagnosed. Initially misdiagnosed patients had a lesser risk of reaching EDSS 4 up to 11 years and EDSS 6 up to 22 years from the onset than non-misdiagnosed patients (p = 0.22 and p = 0.25 correspondingly). Median time to reaching EDSS 4 and 6 was eight years (95% CI 0.0–17.6) and 10 years (95% CI 4.25–20.75) in misdiagnosed and three years (95% CI 0.0–20.0 years) and five years (95% CI 0.0–13.73 years) in non-misdiagnosed patients correspondingly. Conclusions: Initially misdiagnosed RR-MS patients tended to reach disability milestones later than non-misdiagnosed ones, which might reflect an intrinsically milder disease. Individuals presenting with mild or non-specific symptoms suspicious of MS, must be deliberately managed.